Ghana: The politics of legislative debates in a hybrid presidential regime - Sanches, E.; Dias, A. (The politics of legislative debates, 2021)
This chapter investigates the politics of parliamentary debates in Ghana, a country that combines a hybrid presidential regime with a candidate-centered electoral system. Although these features place Ghana as a typical case in which parliamentary rules grant more leeway to individual MPs, our analysis reveals a more complex scenario that defies conventional wisdom. The partial linkage between the legislative and parliamentary branches gives the executive strong agenda-setting powers; moreover, party leadership’s marked influence in the way business in the House unfolds means that there is a skewed playing field, which curtails individual MPs’ access to the floor. The empirical section draws on an original dataset of legislative debates from 2005 through 2019 to examine the determinants of floor access in the Ghanaian parliament. Three findings merit highlighting. First, female MPs are less likely to be selected to speak, and their speeches are significantly shorter when compared to those of male MPs. Second, seniority and exposure to parliament increase the chances of participating in a debate. Third, party leaders have most access to the floor, followed by committee chairs and ministers. However, female MPs who are members of the party leadership speak significantly less than their male counterparts.